The Impact of Compatibility on the Process Integration of the Supply Chain in Improving Firm Performance: The Mediating Effect of Information Technology Capability - Thammarak Srimarut; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
This study investigates the impact of various dimensions of compatibility on the process integration of the supply chain, which leads toward the improvement of firms operational and market performance. Meanwhile, this study also investigates the mediating effect of information technology capabilities between the relationship of supply chain process integration (SCPI) and firm performance. For this purpose, a survey was conducted via a structured questionnaire using online data collection method from the supply chain and production managers of superstores in Thailand. Total of 395 responses were analyzed using structural equation modeling (SEM) to test the hypotheses. The results proved the key important dimensions of compatibility facilitated SCPI, which contribute to the dynamic capability theory. Moreover, IT capabilities also proved as a key mediator, which have a partial influence on the relationship of SCPI and firm performance. Meanwhile, this study potentially contributes to the existing knowledge of supply chain management and open the new dimensions for future scholars to reveal this concept in detail.